Carbon nanotube/carbon composite fiber with improved strength and electrical conductivity via interface engineering. (April 2019) - Zhang, Songlin; Hao, Ayou; Nguyen, Nam; Oluwalowo, Abiodun; Liu, Zhe; Dessureault, Yourri; Park, Jin Gyu; Liang, Richard
Abstract: Carbon nanotube/carbon (CNT/C) composites show potential for lightweight structural materials and non-metal electrical conductors for aerospace, military, and other industries where the combination of lightweight, high strength and excellent conductivity are required. Most research attempts have been reported to fabricate CNT/C composite focusing on the high CNT alignment and dense carbon matrix. However, simultaneous improvement of strength and electrical conductivity in materials still presents a great challenge. In this study, pyrolyzed polydopamine ( py -PDA) with selected surface treatments is introduced as an interface enhancer between CNTs and the carbon matrix. Due to the presence of py -PDA, the effective physical interlocking and conductive pathways are rebuilt at the interface area between CNTs and carbon matrix, resulting in better load transfer and electron transport. The CNT/ py -PDA/C composite fibers demonstrated remarkable improvements in electrical conductivity (2.1 × 10 3 S cm −1 or 228 S m 2 kg −1 ) and tensile strength (up to 727 MPa or 790 MPa/(g·cm −3 )), which should prove to be vastly advantageous as compared to the previously reported CNT/C composites. The outstanding thermal stability of fully carbonized materials is also an attractive feature. Coupled with scalable manufacturing methods, these integrated characteristics of CNT/ py -PDA/C composite fiber can potentially have broad applications for lightweight structural materials and non-metal conductors. Graphical abstract: Image 1